Polyimide dioxime hydrogel film, preparation method thereof and application of polyimide dioxime hydrogel film in uranium adsorption

By modifying the amidoximetated polyacrylonitrile film into a polyimide dioxa hydrogel film, the problems of low adsorption capacity and adsorption rate are solved, and efficient uranium adsorption performance is achieved, with simple process and low cost.

CN119431864APending Publication Date: 2025-02-14HARBIN ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411797954.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing amidoximetyl polyacrylonitrile materials have low adsorption capacity and low adsorption rate.

Method used

By immersing the amidoximetated polyacrylonitrile film in deionized water and heating it to form a polyimide dioxa hydrogel film, improving its adsorption performance.

Benefits of technology

It improves the adsorption capacity and adsorption rate, has good selective adsorption of uranium, and has simple process, low cost, stable material, and is suitable for reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431864A_ABST
    Figure CN119431864A_ABST
Patent Text Reader

Abstract

The invention discloses a polyimide dioxime hydrogel film, a preparation method thereof and application of the polyimide dioxime hydrogel film in uranium adsorption. The invention belongs to the field of uranium adsorption materials. The invention aims to solve the technical problems of low uranium adsorption capacity and low adsorption rate of the existing amidoximated polyacrylonitrile material. The method comprises the following steps: centrifuging an amidoximated polyacrylonitrile solution, dropwise adding supernate onto a substrate, blade-coating, immersing into water, and performing phase-splitting demolding, so as to obtain an amidoximated polyacrylonitrile film; and immersing the film into deionized water, and carrying out heating reaction to obtain the polyimide dioxime hydrogel film. The PAO film is modified through a simple water bath heating method, and the proportion of cyclic imide dioxime functional groups in the modified film is increased, so that the modified film has high adsorption capacity, has good selective adsorption on uranium and is high in adsorption rate. Meanwhile, the preparation process is simple, and the prepared film can keep a complete state in an aqueous solution and is convenient to separate and reuse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of uranium adsorption materials, and in particular relates to a polyimide dioxime hydrogel membrane and a preparation method thereof and application of the membrane in uranium adsorption. Background Art

[0002] Uranium-containing wastewater is radioactive and chemically toxic, so there is an urgent need for an effective and feasible method to treat uranium pollution. Adsorption technology is considered to be one of the most promising methods for removing radioactive uranium from uranium-containing wastewater due to its advantages such as convenient operation, low cost, high treatment efficiency and good selectivity. In recent years, my country has developed a variety of uranium adsorption materials, which can be divided into polymer materials, carbon-based materials, silicate materials, etc. according to the type of matrix. Among the many adsorption materials, a series of compounds containing amidoxime groups are currently recognized as adsorption materials with better adsorption performance.

[0003] Amidoxime contains a unique functional group structure - amine and oxime, which is easy to complex with heavy metal ions, has good adsorption performance and excellent adsorption selectivity for uranyl, and is considered to be one of the best choices for uranium adsorption materials. Amidoxime can be connected to different matrices to obtain adsorption and separation materials. According to the different matrices, it can be roughly divided into monomers and polymers. The first is to obtain it by direct oxime modification of polyacrylonitrile fiber; the second is to perform oxime modification on materials containing acrylonitrile functional groups; ③ Use polyacrylonitrile raw materials to react with hydroxylamine in organic solvents for oxime treatment, and further process the obtained oxime-modified polyacrylonitrile organic solution, such as spinning, to obtain oxime-modified polyacrylonitrile materials. However, the above materials still have problems such as low adsorption capacity and low adsorption rate that need to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems that the existing amidoximated polyacrylonitrile material has low adsorption capacity and low adsorption rate for uranium, and to provide a polyimide dioxime hydrogel membrane and a preparation method thereof and application in uranium adsorption.

[0005] One of the purposes of the present invention is to provide a method for preparing a polyimide dioxime hydrogel film, the method being carried out according to the following steps:

[0006] S1: centrifuge the amidoxime polyacrylonitrile solution, take the supernatant and drip it onto the substrate, apply it by scraping, immerse it in water for phase separation and film removal, take it out and dry it at room temperature to obtain an amidoxime polyacrylonitrile film;

[0007] S2: Immerse the amidoxime-treated polyacrylonitrile film in deionized water and heat it for reaction to obtain a polyimide dioxime hydrogel film.

[0008] It is further defined that the amidoximated polyacrylonitrile solution in S1 is prepared by uniformly mixing N,N-dimethylacetamide, hydroxylamine hydrochloride and anhydrous sodium carbonate, adding polyacrylonitrile and heating to carry out an oximation reaction.

[0009] It is further defined that the molar ratio of hydroxylamine hydrochloride to polyacrylonitrile is 1:1.

[0010] It is further defined that the mass ratio of polyacrylonitrile to N,N-dimethylacetamide is 1:(8-10).

[0011] Further defined, polyacrylonitrile is added after mixing for 2-4 hours.

[0012] It is further defined that the oximation reaction temperature is 60-70°C and the reaction time is 18-24h.

[0013] It is further defined that the centrifugal speed in S1 is 5000-10000 rpm and the time is 4-6 min.

[0014] It is further defined that the heating reaction temperature in S2 is 70-90°C and the time is 6-8h.

[0015] The second object of the present invention is to provide a polyimide dioxime hydrogel film prepared according to the above method.

[0016] The third object of the present invention is to provide an application of the polyimide dioxime hydrogel membrane prepared by the above method in treating uranium-containing wastewater.

[0017] Compared with the prior art, the present invention has the following significant effects:

[0018] (1) The present invention completes the modification of the PAO film by a simple water bath heating method, thereby increasing the proportion of cyclic imide dioxime functional groups in the modified film, so that the modified film has a high adsorption capacity, good selective adsorption of uranium, and a fast adsorption rate.

[0019] (2) The manufacturing process of the present invention is simple, and the prepared film can remain intact in the aqueous solution, which is convenient for separation and reuse.

[0020] (3) The present invention uses PAO film as a base material and modifies it to obtain a more stable hydrogel film material. Compared with the existing method of preparing PAO powder into amidoxime-based fibers, the present invention has the advantages of short preparation cycle, simple preparation method, and low cost. The hydrogel film greatly improves the hydrophilicity of the material, thereby improving the uranium adsorption performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical picture of the PAO film prepared in Example 2;

[0022] Figure 2 This is a physical picture of the modified polyimide dioxime hydrogel film prepared in Example 2;

[0023] Figure 3 is a SEM photo of the PAO film prepared in Example 2;

[0024] Figure 4 This is a SEM photo of the modified polyimide dioxime hydrogel film prepared in Example 2;

[0025] Figure 5a is the N spectrum of the X-ray photoelectron spectrum of the PAO film in Example 2;

[0026] Figure 5b N spectrum of the X-ray photoelectron spectrum of the polyimide dioxime hydrogel film prepared in Example 2;

[0027] Figure 6 This is a comparison chart of the uranium adsorption capacity of the modified polyimide dioxime hydrogel membrane prepared in Examples 1-3 and the PAO film. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0030] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0031] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0032] Embodiment 1:

[0033] The preparation method of the polyimide dioxime hydrogel film of this embodiment is carried out according to the following steps:

[0034] (1) Preparation of casting solution:

[0035] Add 45g of N,N-dimethylacetamide solution and 6.5557g of hydroxylamine hydrochloride into a beaker, stir at room temperature (25°C) until completely dissolved, then add 0.6556g of anhydrous sodium carbonate, stir continuously at room temperature (25°C) for 3h, add 5g of polyacrylonitrile powder, stir evenly, heat in a water bath at 65°C, and magnetically stir for 18h to obtain amidoximated polyacrylonitrile (PAO) solution.

[0036] (2) Film forming and separation drying:

[0037] The PAO solution was centrifuged at a speed of 8000 r / min for 5 minutes, and then the supernatant of the centrifuged PAO solution was taken out with a rubber-tipped dropper and dropped on a glass plate. The casting liquid was scraped to form a uniform coating with a thickness of 1 mm, and then immersed in deionized water at room temperature (25°C) for 2 minutes for phase separation and film removal. After the phase separation was completed, the membrane was taken out and dried at 25°C for 24 hours to obtain a PAO film.

[0038] (3) Polyimide dioxime hydrogel film:

[0039] The dried PAO film was immersed in deionized water at 80°C and heated for reaction at a stirring speed of 500 r / min for 3 hours. The film was then taken out, rinsed with deionized water 3 times, and dried at room temperature (25°C) for 12 hours to obtain a polyimide dioxime hydrogel film.

[0040] Embodiment 2:

[0041] The preparation method of the polyimide dioxime hydrogel film of this embodiment is carried out according to the following steps:

[0042] (1) Preparation of casting solution:

[0043] Add 45g of N,N-dimethylacetamide solution and 6.5557g of hydroxylamine hydrochloride into a beaker, stir at room temperature (25°C) until completely dissolved, then add 0.6556g of anhydrous sodium carbonate, stir continuously at room temperature (25°C) for 3h, add 5g of polyacrylonitrile powder, stir evenly, heat in a water bath at 65°C, and magnetically stir for 18h to obtain amidoximated polyacrylonitrile (PAO) solution.

[0044] (2) Film forming and separation drying:

[0045] The PAO solution was centrifuged at 8000 r / min for 5 min, and then the supernatant of the centrifuged PAO solution was taken with a rubber-tipped dropper and dropped onto a glass plate. The casting solution was scraped to form a uniform coating with a thickness of 1 mm, and then immersed in deionized water at room temperature (25°C) for 2 min for phase separation and film removal. After the phase separation was completed, the film was taken out and dried at 25°C for 24 h to obtain a PAO film. Its macroscopic morphology is shown in FIG. Figure 1 As shown in Figure 1, the PAO film is a light yellow translucent material. The microstructure of the PAO film was characterized, and the results are shown in Figure 1. Figure 3 As shown, it can be seen that the surface of the PAO film is relatively smooth.

[0046] (3) Polyimide dioxime hydrogel film:

[0047] The dried PAO film was immersed in deionized water at 80°C and heated for 7 h at a stirring speed of 500 r / min. The film was then taken out, rinsed with deionized water three times, and dried at room temperature (25°C) for 12 h to obtain a polyimide dioxime hydrogel film with a macroscopic morphology as shown in FIG. Figure 2 As shown. It can be seen that the color of the modified film changes to an opaque off-white color, and the color is uniform, which indicates that the modified film is uniform. The microstructure of the modified film is characterized, and the results are shown in Figure 4 As shown, the surface of the modified film is rough and uneven. The N spectrum comparison of the X-ray photoelectron spectrum of the modified polyimide dioxime hydrogel film and the PAO film is shown in Figure 5. It can be seen that the material has completed the transformation from the amidoxime functional group to the imide dioxime functional group.

[0048] Embodiment 3:

[0049] The preparation method of the polyimide dioxime hydrogel film of this embodiment is carried out according to the following steps:

[0050] (1) Preparation of casting solution:

[0051] Add 45g of N,N-dimethylacetamide solution and 6.5557g of hydroxylamine hydrochloride into a beaker, stir at room temperature (25°C) until completely dissolved, then add 0.6556g of anhydrous sodium carbonate, stir continuously at room temperature (25°C) for 3h, add 5g of polyacrylonitrile powder, stir evenly, heat in a water bath at 65°C, and magnetically stir for 18h to obtain amidoximated polyacrylonitrile (PAO) solution.

[0052] (2) Film forming and separation drying:

[0053] The PAO solution was centrifuged at a speed of 8000 r / min for 5 minutes, and then the supernatant of the centrifuged PAO solution was taken out with a rubber-tipped dropper and dropped on a glass plate. The casting liquid was scraped to form a uniform coating with a thickness of 1 mm, and then immersed in deionized water at room temperature (25°C) for 2 minutes for phase separation and film removal. After the phase separation was completed, the membrane was taken out and dried at 25°C for 24 hours to obtain a PAO film.

[0054] (3) Polyimide dioxime hydrogel film:

[0055] The dried PAO film was immersed in deionized water at 80°C and heated for reaction at a stirring speed of 500 r / min for 11 hours. The film was then taken out, rinsed with deionized water three times, and dried at room temperature (25°C) for 12 hours to obtain a polyimide dioxime hydrogel film.

[0056] Effect Example 1: The modified film obtained in Example 2 was used to measure the uranium adsorption effect. The test process is as follows:

[0057] 0.01 g of polyimide dioxime hydrogel film sample was immersed in 0.2 mol / L NaOH solution at 60 °C for 90 min, then rinsed with deionized water until neutral, and then immersed in uranium solution (40 mL, pH = 5, uranium concentration 5 × 10 -4 mol / L), the concentration of uranium before and after adsorption was measured by spectrophotometer, and the adsorption capacity was calculated as follows:

[0058]

[0059] where q t represents the uranium adsorption capacity within time t, C0 represents the initial uranium concentration; C e represents the concentration of uranium at time t; V represents the volume of the test uranium solution; m represents the mass of the adsorbent (hydrogel membrane).

[0060] The uranium adsorption effects obtained by repeated experiments are shown in Table 1 below:

[0061] Table 1

[0062] frequency Uranium adsorption capacity mg / g 1 462.334 2 458.412 3 474.099 4 474.10

[0063] It can be seen from the above table that the uranium adsorption capacity of the polyimide dioxime hydrogel membrane material is as high as 474 mg / g and can be used multiple times.

[0064] Effect Example 2: The modified film obtained in Example 1-3 was used to measure the uranium adsorption effect. The test process is as follows:

[0065] 0.01 g of the polyimide dioxime hydrogel film samples obtained in Examples 1-3 were taken respectively, immersed in 0.2 mol / L NaOH solution, treated with alkali for 90 min at 60 °C, then rinsed with deionized water until neutral, and then immersed in uranium solution (40 mL, pH = 5, uranium concentration 5 × 10 -4 mol / L), the concentration of uranium before and after adsorption was measured by spectrophotometer, and the adsorption capacity was calculated by formula (1). The results are shown in Table 2 below:

[0066] Table 2

[0067]

[0068]

[0069] It can be seen from the above table that the optimal modification time of PAO film in 80℃ deionized water is 7h.

[0070] Effect Example 3: The modified films obtained in Examples 1-3 and the PAO films in the examples were used to measure the uranium adsorption effect. The test process is as follows:

[0071] 0.01 g of the polyimide dioxime hydrogel film obtained in Examples 1-3 and the PAO film sample in the example were taken and immersed in 0.2 mol / L NaOH solution at 60 °C for 90 min, then rinsed with deionized water until neutral, and then immersed in uranium solution (40 mL, pH = 5, uranium concentration 5 × 10 -4 mol / L), and the concentration of uranium before and after adsorption was measured by spectrophotometer. The results are as follows Figure 6 As shown by Figure 6 It can be seen that the adsorption capacity of the modified material is increased by 72.74% compared with that before modification (274.46 mg / g).

[0072] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a polyimide dioxime hydrogel film, characterized in that: The method: S1: centrifuge the amidoxime polyacrylonitrile solution, take the supernatant and drip it onto the substrate, apply it by scraping, immerse it in water for phase separation and film removal, take it out and dry it at room temperature to obtain an amidoxime polyacrylonitrile film; S2: Immerse the amidoxime-treated polyacrylonitrile film in deionized water and heat it for reaction to obtain a polyimide dioxime hydrogel film.

2. The method according to claim 1, characterized in that The amidoximation polyacrylonitrile solution in S1 is prepared by uniformly mixing N,N-dimethylacetamide, hydroxylamine hydrochloride and anhydrous sodium carbonate, adding polyacrylonitrile and heating to carry out an oximation reaction.

3. The method according to claim 2, characterized in that The molar ratio of hydroxylamine hydrochloride to polyacrylonitrile is 1:

1.

4. The method according to claim 2, characterized in that: The mass ratio of polyacrylonitrile to N,N-dimethylacetamide is 1:(8-10).

5. The method according to claim 2, characterized in that: After mixing for 2-4 hours, add polyacrylonitrile.

6. The method according to claim 2, characterized in that The oximation reaction temperature is 60-70°C and the time is 18-24h.

7. The method according to claim 1, characterized in that The centrifugal speed in S1 is 5000-10000 rpm and the time is 4-6 min.

8. The method according to claim 1, characterized in that The heating reaction temperature in S2 is 70-90°C and the time is 6-8h.

9. The polyimide dioxime hydrogel film prepared by the method according to any one of claims 1 to 8.

10. Use of the polyimide dioxime hydrogel membrane according to claim 9 in treating uranium-containing wastewater.